1984
DOI: 10.1007/bf00587544
|View full text |Cite
|
Sign up to set email alerts
|

Mode of regulation of the ACh-sensitive K-channel by the muscarinic receptor in rabbit atrial cells

Abstract: The mechanism underlying the regulation of the K-channel by the muscarinic receptor was examined with patch-clamp experiments in atrial cells isolated enzymatically from the rabbit heart. The patch-electrode and the recording chamber were perfused with various solutions while the activity of the K-channels in the membrane-patch was recorded continuously. In the absence of muscarinic agonists, opening of K-channels occurred at a low frequency (basal activity). Application of ACh to the bath did not affect the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
223
1
1

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(246 citation statements)
references
References 28 publications
21
223
1
1
Order By: Relevance
“…Basal tone may be an important component of muscarinic (and other receptor) physiology. In fact, it has been shown that treatment of atrial cell membranes with muscarinic antagonists blocks spontaneous K + channel opening and G-protein activity [24,25]. Our observations imply that the control of G-protein expression may profoundly contribute to these phenomena.…”
Section: R ~ R* + G ~ R*g ---R Responsementioning
confidence: 57%
“…Basal tone may be an important component of muscarinic (and other receptor) physiology. In fact, it has been shown that treatment of atrial cell membranes with muscarinic antagonists blocks spontaneous K + channel opening and G-protein activity [24,25]. Our observations imply that the control of G-protein expression may profoundly contribute to these phenomena.…”
Section: R ~ R* + G ~ R*g ---R Responsementioning
confidence: 57%
“…Also it remains unclear to what extent G proteins sustain a spontaneous agonist-independent activation under in vivo conditions. If not negligible, this basal G protein activation is likely to affect adenylyl cyclase and IK(ACh) Interestingly, it has been shown that single mAChR-activated K+ channels can open spontaneously even in the absence of mAChR stimulation (Soejima & Noma, 1984;Kaibara, Nakajima, Irisawa & Giles, 1991;Okabe et al 1991;Ito et al 1991) and that this spontaneous activity can be totally suppressed by pertussis toxin pretreatment (but see Kaibara et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…However, in a later study performed on isolated cardiac myocytes, atropine was also found to produce mAChR agonist-independent effects (Soejima & Noma, 1984) which could not be easily explained by a contamination by endogenous ACh. Indeed Soejima & Noma (1984) found that in isolated myocytes from rabbit atrium, atropine inhibits the spontaneous IK(ACh) single channel activity. However, this finding is contradicted by the observation that in guinea-pig atrial cells, basal activity of IK(ACh) channels was not affected by atropine (Okabe, Yatani & Brown, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies, the kinetic analysis of the muscarinic K+ channel openings in several mammalian species showed mean open times of -1 ms and the singlechannel conductances between 35-40 pS at symmetrical 140 mM-K' (Sakmann, Noma & Trautwein, 1983;Soejima & Noma, 1984;Kurachi et al 1986; Logothetis,134 D. KLiTI MUSCARINIC K+ CHANNEL MODULATION Kurachi, Galper, Neer & Clapham, 1987;Kim, Lewis, Graziadei, Neer, Bar-Sagi & Clapham, 1989). However, these studies have not examined the early activation of the K+ channel by ACh.…”
Section: Introductionmentioning
confidence: 95%